Sull'immagine sonora della città - Antonella Radicchi (Premio Ricerca «Città di Firenze», 2012)
The dissertation deals with the contemporary city soundscape and fits into the disciplinary field of sensuous urbanism, soundscape studies and emotional geography. The key term, soundscape, is to be understood as all the sounds that surround us, as a perceptual theme, that is, object of a subject's perception, in its sense of 'landscape' including the metaphorical meaning of an emotional or mnemonic emotional soundscape. The dissertation is structured in two parts: the first and second chapters define the disciplinary spheres of sensory urbanism and soundscape studies, while the third and fourth chapters explore the forms that classical sound environment analysis and planning tools take on within the aforesaid disciplinary fields. Finally, the conclusions give a methodological indication aimed at favouring the integration of soundscape studies within the town planning discipline, and propose «tender sound map» and «sound niche» operating tools to help achieve the goal of planning the contemporary city's physical and sound spaces at the same time.